2020
DOI: 10.21873/invivo.11989
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Prognostic Score (GPS) and Tumor Response as Biomarkers of Nivolumab Monotherapy in Third- or Later-line Setting for Advanced Gastric Cancer

Abstract: Background/Aim: This study aimed to seek clinical biomarkers of nivolumab monotherapy for advanced gastric cancer (AGC) of which efficacy is limited. We focused on Glasgow Prognostic Score (GPS), which reflects systemic inflammatory and nutritional status as well as disease control by chemotherapy immediately before nivolumab (DCBC). Patients and Methods: AGC patients with measurable lesions who were treated with nivolumab in the third-or later-line were included. DCBC was defined as a best overall response of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Kurosaki et al [ 24 ] reported that a higher GPS was significantly associated with a shorter PFS (median, 3.0 months vs. 1.6 months vs. 1.4 months for a GPS of 0 vs. 1 vs. 2, respectively; p=0.005) and OS (median, 11.0 months vs. 5.1 months vs. 2.9 months for a GPS of 0 vs. 1 vs. 2, respectively; p < 0.001) in 80 patients with advanced gastric cancer treated with nivolumab. Kurosaki et al [ 24 ] also reported that a high baseline NLR, indicating neutrophilia and lymphopenia, and low PNI were significantly associated with worse PFS and OS in 102 patients with advanced NSCLC treated with anti-PD-1 inhibitors (median PFS, 3.2 months for the high-NLR group vs. 7.3 months for the low-NLR group, p=0.009, and 3.3 months for the low-PNI group vs. 6.3 months for the high-PNI group, p=0.007; median OS, 3.7 months for the high-NLR group vs. 9.8 months for the low-NLR group, p=0.002, and 4.2 months for the low-PNI group vs. 11.5 months for the high-PNI group, p < 0.001) [ 25 ]. Interestingly, in our study, the NLR played a role as a predictor of PFS and OS when considered as a change after one cycle of ICIs, but not the baseline value (which was significant in the univariate analysis for PFS and OS, but not in the multivariate analysis).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kurosaki et al [ 24 ] reported that a higher GPS was significantly associated with a shorter PFS (median, 3.0 months vs. 1.6 months vs. 1.4 months for a GPS of 0 vs. 1 vs. 2, respectively; p=0.005) and OS (median, 11.0 months vs. 5.1 months vs. 2.9 months for a GPS of 0 vs. 1 vs. 2, respectively; p < 0.001) in 80 patients with advanced gastric cancer treated with nivolumab. Kurosaki et al [ 24 ] also reported that a high baseline NLR, indicating neutrophilia and lymphopenia, and low PNI were significantly associated with worse PFS and OS in 102 patients with advanced NSCLC treated with anti-PD-1 inhibitors (median PFS, 3.2 months for the high-NLR group vs. 7.3 months for the low-NLR group, p=0.009, and 3.3 months for the low-PNI group vs. 6.3 months for the high-PNI group, p=0.007; median OS, 3.7 months for the high-NLR group vs. 9.8 months for the low-NLR group, p=0.002, and 4.2 months for the low-PNI group vs. 11.5 months for the high-PNI group, p < 0.001) [ 25 ]. Interestingly, in our study, the NLR played a role as a predictor of PFS and OS when considered as a change after one cycle of ICIs, but not the baseline value (which was significant in the univariate analysis for PFS and OS, but not in the multivariate analysis).…”
Section: Discussionmentioning
confidence: 99%
“…nivolumab[24].Kurosaki et al also reported that a high baseline NLR, indicating neutrophilia Korean Cancer AssociationThis article is protected by copyright. All rights reserved.…”
mentioning
confidence: 97%
“…Accumulating studies have elucidated that GPS can be a potent and reliable prognostic biomarker in GC and as a predictive factor for adjuvant chemotherapy in gastric cancer patients after curative surgery [ 29 ], for which the immune response has been implicated as a key determinant. GPS has been reported to correlate with elevated cytokine levels, adipokine levels, drug metabolism, weight and muscle loss, and poor performance status [ 30 ]. These factors may be related to the immune status of the host, and they may affect the efficacy of antitumor immunity therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates that angiogenesis and immunosuppression frequently occur simultaneously during tumor growth and evolution through constant crosstalk with the surrounding microenvironment [ 31 ]. Recent study suggests that mGPS may serve as a biomarker to reflect sensitivity to immune checkpoint inhibitors in advanced GC and renal cancer [ 30 , 32 ]. However, no other study has explored whether mGPS can be used for predicting postoperative survival in GC patients with normal CEA and CA19-9.…”
Section: Discussionmentioning
confidence: 99%
“…In a word, gastric cancer patients with malnutrition and system inflammation status tended to have higher metastasis rates and shorter survival times. Numerous previous studies have shown that composite indexes based on serum markers such as the Controlling Nutritional Status (CONUT) score, Glasgow Prognostic Score (GPS), and neutrophil-lymphocyte ratio (NLR) could both predict the prognosis of patients with gastric cancer (27)(28)(29). In addition, their ability to predict the prognosis of patients with gastric cancer who received ICIs has also been further confirmed.…”
Section: Introductionmentioning
confidence: 99%